Posterior mitral annuloplasty for enhancing mitral leaflet coaptation: using a strip designed for placement in the posterior annulus. Issue 1 (December 2015) - Kim, Jong; Kim, Kyung; Choi, Jong; Kuh, Ja
Abstract Background In patients with mitral valve regurgitation (MR), posterior mitral annuloplasty (PMA) was performed for mitral valve repair using a strip designed for placement in the posterior annulus, sparing the anterior annulus and anterior half of the commissures. Methods Between September 2009 and October 2013, we performed PMA using a novel strip in 74 consecutive patients with MR greater than 3+. Procedures associated with mitral valve repairs were performed in 41 patients (56.9 %), including new chord placement for leaflet prolapse (n =30), patch valvuloplasty for posterior chord rupture (n =4), and posterior leaflet augmentation (n =15). All patients were analyzed by serial echocardiographic follow-up, and preoperative and postoperative computed tomography was performed in 10 randomly selected patients. Results Hospital death occurred in two patients (2.7 %), and 72 survived patients were completely followed up. At a mean follow-up of 37.2 ± 15.0 months, the MR grade was zero or 1+ in 64 patients (88.9 %), 2+ in 7 patients (9.7 %), and 3+ in one patient (1.4 %). The mean indexed valve area and mean valve gradient were 1.7 ± 0.4 cm2 /m2 and 3.5 ± 1.2 mmHg, respectively. The mean leaflet coaptation height in early systole was 12.8 ± 3.5 mm. During the cardiac cycle, the repaired valves exhibited dynamic changes of 19.5 ± 9.3 % in the septo-lateral dimensions. No early conversions to valve replacements or late reoperations occurred. None of the patients with remnant or recurrent MR experienced hemolysis. Conclusions PMA using a novel strip showed a sufficient coaptation height secondary to reduction of the septo-lateral annular dimensions and dynamic changes in the dimensions. It can be expected to be an alternative mitral annuloplasty technique with satisfactory results.